2017
DOI: 10.1136/gutjnl-2017-314190
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative burden of inflammation predicts colorectal neoplasia risk in ulcerative colitis: a large single-centre study

Abstract: ObjectiveUlcerative colitis (UC) is a dynamic disease with its severity continuously changing over time. We hypothesised that the risk of colorectal neoplasia (CRN) in UC closely follows an actuarial accumulative inflammatory burden, which is inadequately represented by current risk stratification strategies.DesignThis was a retrospective single-centre study. Patients with extensive UC who were under colonoscopic surveillance between 2003 and 2012 were studied. Each surveillance episode was scored for a severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 20 publications
4
136
2
2
Order By: Relevance
“…3,5,6 Commonly referred to as "pseudopolyps," PIPs are encountered in 20%-45% of patients with IBD and colonic involvement. [7][8][9][10] Previous case-control studies reported a 1.9-to 2.5-fold increased risk of CRC in patients with PIPs. 8,9,11 More recently, however, in a large retrospective cohort study of patients with ulcerative colitis (UC) undergoing CRN surveillance, PIPs did not independently predict CRN or predict progression from low-grade dysplasia (LGD) to advanced CRN (ACRN; defined as high-grade dysplasia [HGD] or CRC).…”
Section: Background and Aimsmentioning
confidence: 99%
“…3,5,6 Commonly referred to as "pseudopolyps," PIPs are encountered in 20%-45% of patients with IBD and colonic involvement. [7][8][9][10] Previous case-control studies reported a 1.9-to 2.5-fold increased risk of CRC in patients with PIPs. 8,9,11 More recently, however, in a large retrospective cohort study of patients with ulcerative colitis (UC) undergoing CRN surveillance, PIPs did not independently predict CRN or predict progression from low-grade dysplasia (LGD) to advanced CRN (ACRN; defined as high-grade dysplasia [HGD] or CRC).…”
Section: Background and Aimsmentioning
confidence: 99%
“…Since old people show an increased baseline risk of infections and cancer, older patients are less likely to receive biologics . Additionally, the risk of infection and cancer is associated with disease activity . For these reasons, collecting and appraising the evidence concerning the potential harms associated with use of biologics in elderly IBD patients is very important .…”
Section: Introductionmentioning
confidence: 99%
“…While endoscopic surveillance for dysplasia is a key component of chronic UC management, field cancerisation effects secondary to inflammation may be more effectively attenuated by chemoprevention. Recent work suggests that it is cumulative inflammatory burden which contributes to development of CRC, thus in theory any drug preventing inflammation might mediate this risk . Whether there are specific chemopreventive benefits for aminosalicylates is unclear .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that it is cumulative inflammatory burden which contributes to development of CRC, thus in theory any drug preventing inflammation might mediate this risk. 66 Whether there are specific chemopreventive benefits for aminosalicylates is unclear. 67 It has been hypothesised that aminosalicylates may specifically reduce colorectal dysplasia risk secondary to activation of peroxisome proliferator-activated receptor-γ, 68 free radical scavenging, 69 or inhibition of the Wnt/β-catenin pathway.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%